Mikhail Gorbachev - Moga, Jerome; Nang Chan Yeema (New York, USA A Bantam Skylark Book, 1991)
Provides a life journey of Mikhail Gorbachev from his boyhood to how he won the Red Banner for Labor when he was a teenager.
Keywords: Biography